Car Service Record System - HAIROL RIZAL, MUHAMMAD IMRAN; OMAR, DR NURUL ASWA (Applied Information Technology And Computer Science, 2026)
Vehicle service workshops that rely on manual methods often face difficulties in managing operations efficiently. These challenges can negatively affect both workshop staff and customer satisfaction.To overcome these issues, a systematic and digital approach is proposed to replace the existing manual system.The method used is waterfall method to ensure the development process is fully successful. This project utilizes Visual Studio Code as the development environment and XAMPP as the local server platform to build a structured and organized car service recording system. The system is designed with a proper data hierarchy to streamline the management process. As a result, a complete and functional system has been successfully developed. The system addresses the core problems faced by the workshops and improves their operational efficiency. Overall, it facilitates better management of daily activities and enhances the service experience for customers.